Pathomorphological characteristics of cerebellum hemisphere dosed traumatic injury model in the experiment - V. I. Tsymbalyuk; V. M. Semenova; Yu. Yu. Senchyk; V. V. Medvedev (Ukrainian Neurosurgical Journal, 2010)
The improved method of rat’s cerebellum traumatic injury by means of direct mechanical stroke through undamaged hard cerebral membrane (cover) above external surface of cerebellum left hemisphere with registration of injuring factor’s strength is described in details. Morphological peculiarities of traumatic process of different heaviness in cerebellum tissue are researched. Taking into consideration data of morphological control optimal indices of stroke strength have been chosen to achieve a stable neurological deficit and injury focus forming in the cerebellum left hemisphere at high homogeneity among animals in experimental group.